'Rolling the Dice': Barriers to Effective Summary Diversion in the Northern Territory. Issue 1 (2nd January 2016) - Pyne, Anthony
Abstract : Diverting mentally ill defendants away from the court and into treatment is an important way the criminal justice system protects society. The current summary diversion process in the Northern Territory is cumbersome, risky and time-consuming. Procedural hurdles mean that legislative provisions designed to divert people into treatment are virtually never used. Defendants usually apply for their charges to be completely dismissed. The result is a disappointing zero sum game about whether the defendants should be 'let off' or dealt with in the regular court process, where they may face a mandatory sentence. If mentally ill defendants are to be effectively diverted, the process needs to be reformed.